Measurement of Cr Evaporation at 760 °C for Several Nickel Based Alloys at Moderate Velocities. (5th January 2017) - Tylczak, Joseph H; Holcomb, Gordon R
Abstract : The effect of gas speed on chromium loss, which is significant in a high temperature alloy's lifetime, was explored. Cr loss rate at 760 °C, in a combined air and 57 vol pct water environment with an apparent gas flow rate of 26.5 m·s -1 were measured for durations up to 1, 000 h. Three alloys were investigated, HAYNES 230, 282, and Inconel 625. Samples were measured gravimetrically and examined via scanning electron microscopy. While the exposed surfaces were quite similar between the static and the moving samples, the degree of depletion of Cr in the metal near the surface and the gravimetric losses were significant. At 1, 000 h, both the HAYNES 230 and Inconel 625 moving samples had lost about twice the mass of their respective static samples. Analysis showed Cr depletion was always deeper in the moving samples compared to their static equivalents.